Gold price determinants during selected economic crises - Chepelau, Andrej; Jedlinský, Jakub; Mazánková, Zuzana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2021)
The goal of this thesis is to find out which factors that are believed to be strong determinants of the price of gold in the long-run still determine the price of gold in the short-run of economic crises. The theoretical part firstly goes through the various aspects of gold. Then, through literature review, the determinants that are often believed to be determinants of the price of gold in the long-run are found. Then I describe the various methodological approaches in particular literature sources and follow with a description of my approach. The practical part consists of the analysis of chosen determinants and their effect on the price of gold. The findings indicate that the determinants that are generally believed to be important factors of the pricing of gold, in the long run, do not necessarily hold the same relationship during economic crises.
Vedoucí práce: Jakub Jedlinský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses